Airborne SARS‐CoV‐2 surveillance in hospital environment using high‐flowrate air samplers and its comparison to surface sampling. (14th September 2021) - Ang, Alicia XY; Luhung, Irvan; Ahidjo, Bintou A.; Drautz‐Moses, Daniela I.; Tambyah, Paul A.; Mok, Chee Keng; Lau, Kenny JX; Tham, Sai Meng; Chu, Justin Jang Hann; Allen, David M.; Schuster, Stephan C.
Abstract: Reliable methods to detect the presence of SARS‐CoV‐2 at venues where people gather are essential for epidemiological surveillance to guide public policy. Communal screening of air in a highly crowded space has the potential to provide early warning on the presence and potential transmission of SARS‐CoV‐2 as suggested by studies early in the epidemic. As hospitals and public facilities apply varying degrees of restrictions and regulations, it is important to provide multiple methodological options to enable environmental SARS‐CoV‐2 surveillance under different conditions. This study assessed the feasibility of using high‐flowrate air samplers combined with RNA extraction kit designed for environmental sample to perform airborne SARS‐CoV‐2 surveillance in hospital setting, tested by RT‐qPCR. The success rate of the air samples in detecting SARS‐CoV‐2 was then compared with surface swab samples collected in the same proximity. Additionally, positive RT‐qPCR samples underwent viral culture to assess the viability of the sampled SARS‐CoV‐2. The study was performed in inpatient ward environments of a quaternary care university teaching hospital in Singapore housing active COVID‐19 patients within the period of February to May 2020. Two types of wards were tested, naturally ventilated open‐cohort ward and mechanically ventilated isolation ward. Distances between the site of air sampling and the patient cluster in the investigated wards were also recorded. No successful detection of airborne SARS‐CoV‐2 was recorded when 50 L/min air samplers were used. Upon increasing the sampling flowrate to 150 L/min, our results showed a high success rate in detecting the presence of SARS‐CoV‐2 from the air samples (72%) compared to the surface swab samples (9.6%). The positive detection rate of the air samples along with the corresponding viral load could be associated with the distance between sampling site and patient. The furthest distance from patient with PCR‐positive air samples was 5.5 m. The airborne SARS‐CoV‐2 detection was comparable between the two types of wards with 60%–87.5% success rate. High prevalence of the virus was found in toilet areas, both on surfaces and in air. Finally, no successful culture attempt was recorded from the environmental air or surface samples.